2017
DOI: 10.3390/ijms18030514
|View full text |Cite
|
Sign up to set email alerts
|

Derivate Isocorydine (d-ICD) Suppresses Migration and Invasion of Hepatocellular Carcinoma Cell by Downregulating ITGA1 Expression

Abstract: In our previous studies, we found that isocorydine (ICD) could be a potential antitumor agent in hepatocellular carcinoma (HCC). Derivate isocorydine (d-ICD), a more effective antitumor agent, has been demonstrated to inhibit proliferation and drug resistance in HCC. In order to investigate the potential role of d-ICD on HCC cell migration and its possible mechanism, wound healing assay, trans-well invasion assay, western blot analysis, and qRT-PCR were performed to study the migration and invasion ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…The role of integrin α1 in HCC metastasis is currently unclear. Liu et al (25) detected a positive correlation between integrin α1 and migration and invasion, which is in accordance with the present study. However, compared with the present investigation, adhesion assays were not conducted.…”
Section: Suppression Of Adhesion By Everolimus and Temsirolimussupporting
confidence: 93%
“…The role of integrin α1 in HCC metastasis is currently unclear. Liu et al (25) detected a positive correlation between integrin α1 and migration and invasion, which is in accordance with the present study. However, compared with the present investigation, adhesion assays were not conducted.…”
Section: Suppression Of Adhesion By Everolimus and Temsirolimussupporting
confidence: 93%
“…The identification of ITGA1 was involved in cell invasion and metastasis in hepatocellular carcinomas [27]. In our study, we demonstrated that ITGA1 was highly expressed in CRC tumors.…”
Section: Discussionsupporting
confidence: 54%
“…Palmatine (PMT) has been confirmed to possess antibacterial, antifungal, antivirus and anti‐inflammatory activities in vitro and in vivo (Chao et al, ; Kim et al, ; Kong, Zhao, Xiao, Li, & Ren, ; Singh & Kakkar, ; Yan, Jin, Xiao, & Dong, ). The anticancer activities of isocorydine (ICD) and its derivatives have been investigated for cytotoxicity and their interaction with DNA and topoisomerases (Hoet et al, ), also supported by our work (Chen et al, ; Li et al, ; Liu et al, ; Lu et al, ; Sun et al, ; Yan et al, ; Zhong et al, ). ICD also has potential antiviral and antiparasitic activities (Montenegro et al, ).…”
Section: Introductionsupporting
confidence: 69%